Estimation of relatedness among non-pedigreed Yakutian cryo-bank bulls using molecular data : implications for conservation and breed management - Tapio, Ilma; Tapio, Miika; Li, Menghua; Popov, Ruslan; Ivanova, Zoya; Kantanen, Juha (Genetics Selection Evolution, 2010)
v 2010 ok Abstract